Study of the application potential of synthetic and natural polymeric coatings in stem cell research - Perestrelo, Ana Rubina (2015)
Self-renewability and the ability to differentiate into various functional cells are characteristics of embryonic stem cells (ESCs) that make them attractive for applications in biomedical field, namely in restoring the function of damaged cells/tissues. In research, ESCs are usually cultured in gelatin or over a monolayer of mitotically inactivated mouse embryonic fibroblasts (MEFsi). The latter is the gold standard to maintain pluripotent ESCs in culture. A variety of alternative technologies have been suggested to control stem cell fate and function, but examples of versatile, non-animal derived and inexpensive materials able to support pluripotent ESCs are limited. To circumvent this, we aimed to find a biomaterial able to support pluripotent ESC cultures that would avoid the laborious and time consuming parallel culture of MEFsi and as simple to handle as gelatin. There is an increasing interest in regulating stem cells under a specific microenvironment using biomaterials as artificial extracellular matrices (ECMs) to control their self-renewability and differentiation capacity. In the present work we developed and tested the applicability of two biomaterials, one natural and one synthetic polymer, to support mouse ESC (mESC) culture. Accordingly, undifferentiated mESCs were cultured in coatings of Locust Bean Gum (LGB) and of a new synthetic nanofiber (nf) material based on the self-assembly of a triblock copolymer, poly (ethyleneglycol-β-trimethylsilyl methacrylate-β-methacrylic acid), conjugated with the peptide Glycine-Arginine-Glycine-Aspartate-Serine. According to our data, compared to conventional stem cell culture methodologies, ESCs grown in LBG and nanofiber coatings maintained their self-renewability and trilineage differentiation capacity even after long term culture. In parallel, this work also comprises the functional study of collagen and calciumbinding EGF domains 1 (Ccbe1) using primary fibroblasts as a tool. It has been shown that Ccbe1 is involved in lymphangiogenesis, cardiogenesis and carcinogenesis, however, its function and molecular action remains unknown. The data presented here suggests that Ccbe1 coordinates cell adhesion, migration and proliferation, thus playing a key role in the ECM.